FAKTOR-FAKTOR YANG MEMENGARUHI NILAI INTERDIALYTIC WEIGHT GAIN PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RUANG DIALISIS RSUD ARIFIN ACHMAD PROVINSI RIAU - Pratama, Tirta Arya; Irwan, Muhammad; Fentia, Lia (Ensiklopedia of Journal, 2025)
Abstract: Chronic Kidney Failure (CKD) is a progressive, end-stage kidney disease in which the body is unable to maintain metabolic, fluid and electrolyte balance, resulting in uremia. This can lead to an increase in body weight between dialysis sessions, commonly referred to as interdialytic weight gain (IDWG). The purpose of this study was to determine the factors influencing IDWG in patients with GKD undergoing hemodialysis at the dialysis unit of Arifin Achmad Hospital, Riau Province. This research method is descriptive correlation with cross-sectional approach. The sample of this study were patients undergoing hemodialysis in Arifin Achmad Hospital Riau Province with sampling using accidental sampling technique, which amounted to 61 patients. Data were collected using a questionnaire consisting of patient characteristics, family support, HD adherence, fluid restriction adherence, and stress level. There is no relationship between HD compliance and increased IDWG levels. On the contrary, there is a relationship between family support, fluid restriction compliance, and stress level among hemodialysis patients at Arifin Achmad Hospital, Riau Province. It is hoped that this study can provide knowledge and input as well as an overview of IDWG values in hemodialysis patients. Keywords: Family Support, HD Adherence, Fluid Restriction Adherence, Stress Level, IDWG